The Role of Self-Efficacy in Mediating the Effect of Entrepreneurial’s Knowledge, Personality and Family Circles Against the Enterprise’s Interest - Sudjarwo, Ragil; Wahyudin, Agus; Sudarma, Ketut (Universitas Negeri Semarang, 2019)
The objective of this research was to find out the effect of entrepreneurs knowlede, personality, and family circles against the enterprise’s interest. Moreover, this research aimed to find out how the intervening variable that was self-eficacy could influence the entrepreneurs knowledge, personality, and family circles into the enterprise’s interest. This research used quantitative method. The subjects of this study were 83 participants from 5 SKB in enterpreneurship skills education courses who had undergone the education and training process in the discricts and cities of Semarang. Collecting the data was questionnaire. The method of analysing the data was percentage descriptive, path analysis and sobel test. The result of the research showed that the variables of entrepreneurs knowledge, personality, and family circles influenced the enterprise’s interest. The result of path test explained that the variables of entrepreneurs knowledge, personality, and family circles could use self-efficacy varible as the mediation because the total effect of each independent variable was larger than the dirrect one. The suggestion for this research is the participants must be actively involved in various activities which can strengthen the interest of becoming the successful entrepreneurs and pay attention to the activities of business people or entrepeneurs who have succeeded around them that can be used as a reference in developing business. In addition, SKB is expected to be able to take the right policy breakthrough in order to increase the entrepreneurship’s interest of the participants in entrepreneurship skils education courses.